Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10530-008-9292-4
|View full text |Cite
|
Sign up to set email alerts
|

Tackling aquatic invasions: risks and opportunities for the aquarium fish industry

Abstract: The aquarium trade is an important and rapidly growing vector for introduced species in the United States. We examined this vector by surveying pet stores in the San Francisco Bay-Delta region to compile a list of aquarium fish species commonly stocked. We identified which of these species might be able to survive in the Bay-Delta, and investigated store representatives' knowledge and attitudes about biological invasions. A restrictive analysis using conservative estimates of fish temperature tolerances and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 18 publications
1
62
0
1
Order By: Relevance
“…These are further subdivided into six principal pathway categories: intentional release, escape from containment, transport as a contaminant, transport as a stowaway, spread through corridors, and spread through unaided natural dispersal . Application of this framework to 500 invasive alien species in the Global Invasive Species Database revealed, for example, that horticultural and pet and aquarium escapees were the most frequent pathways by which invasive species are introduced and spread (Chang et al 2009;Roy et al 2014). Parties to the CBD have called for the use of this pathway framework for the purpose of assessing and prioritizing the risk posed by pathways (UNEP 2014), which will facilitate the reporting envisaged in Aichi Target 9.…”
Section: Prioritizing Invasion Pathwaysmentioning
confidence: 99%
“…These are further subdivided into six principal pathway categories: intentional release, escape from containment, transport as a contaminant, transport as a stowaway, spread through corridors, and spread through unaided natural dispersal . Application of this framework to 500 invasive alien species in the Global Invasive Species Database revealed, for example, that horticultural and pet and aquarium escapees were the most frequent pathways by which invasive species are introduced and spread (Chang et al 2009;Roy et al 2014). Parties to the CBD have called for the use of this pathway framework for the purpose of assessing and prioritizing the risk posed by pathways (UNEP 2014), which will facilitate the reporting envisaged in Aichi Target 9.…”
Section: Prioritizing Invasion Pathwaysmentioning
confidence: 99%
“…For example, human population density and economic development of areas is correlated with exotic species introductions (Gallardo, 2014;Gallardo and Aldridge, 2013;Perdikaris et al, 2012), including crayfish (Chucholl, 2014). The pet trade has been responsible for many introductions of non-native species (Chang et al, 2009;Duggan, 2010;Keller and Lodge, 2009;Strecker et al, 2011), and is likely the major driver of introductions of non-indigenous crayfish in several countries (Chucholl, 2013;Soes and Koese, 2010). The scale of the trade in pets, particularly aquatic animals, has been difficult to estimate (Rhyne et al, 2012), but online sale and trade websites can provide estimates of the risk of introduction of non-indigenous species (Kikillus et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Patoka et al (2014b) found 3.6% of crayfish owners released them, either into natural habitats (2.1%) or the sewers (1.5%). While most surveys show people support prevention of invasive species (e.g., Chang et al, 2009;Bohman & Edsman, 2011), about 70% of the releases are associated with convenience, rather than consideration of the environment (Drake et al, 2015). However, about 30% of risky behaviour is unpredictable (Drake et al, 2015).…”
Section: Risk Assessment Techniquesmentioning
confidence: 99%
“…Store surveys for fish showed differences between store types: chain stores were more likely to have species identification of fish being sold, and those identifications were more likely to be correct (Chang et al, 2009).…”
Section: Contact With Retailersmentioning
confidence: 99%
See 1 more Smart Citation